Calcificated degenerative aortal stenosis: clinical and instrumental parameters - N. A. Shostak; N. Yu. Karpova; M. A. Rashid; D. V. Piskunov; M. E. Yadrov (Российский кардиологический журнал, 2006)
The article is devoted to complex assessment of several clinical and instrumental parameters inpatients with calcificated degenerative aortal stenosis (CDAS) of varying severity. The main group included 101CDAS patients, the control group - 32 individuals with coronary heart disease (CHD)) and / or arterial hypertension, but without aortal valve pathology, according to echocardiography data. Aortal stenosis progression was associated with increased prevalence of angina pain syndrome, paroxysmal night dyspnoe, vertigo, atypical systolic murmur, and aortal regurgitation. Hotter monitoring demonstrated myocardial ischemia in 32, 6 % of CDAS patients, and stair test - in 66, 6 % (painless ischemia in 57, 6 % of the cases). Physical stress tolerance decreased as aortal stenosis severity increased.